Fizyk jako element aksjosfery czasów Związku Radzieckiego (na przykładzie reportaży Hanny Krall i Jacka Hugo-Badera) - Słupianek-Tajnert, Daria (Studia Rossica Posnaniensia, 2021)
The article attempts to analyse the conceptualisation of the scientist-physicist based on the examples of selected reportages by Hanna Krall and Jacek Hugo-Bader. The analysis was conducted in an axiolinguistic key and its aim was to confirm the thesis about the important role of physicists in the Soviet axiosphere. It can be observed that in the axiological profile of a physicist, obtained on the basis of an empirical analysis, instrumental values dominate and these are closely connected with the fact that physicists are associated with political interests. Physicists, who function as objects of evaluation in the analysed reportages, are also a means of an indirect evaluation in relation to the political system in the USSR and reflect ways in which the country treats its citizens. The empirical material analysed allows us to conclude that within the Russian linguistic-cultural area, the physicist does not refer us only to a scientist dealing with a specific research discipline, but deserves to be called a concept that reflects a characteristic stage of the social and political life of the USSR, permanently inscribed into the axiosphere of that period.